Motivasi, Pola Komunikasi dan Tantangan Komisi Informasi Dalam Penyelesaian Sengketa Informasi (Studi Kasus di Provinsi Kalimantan Selatan) - Hartiningsih (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2017)
Law No. 14 of 2008 on the Transparency of Public Information (KIP) of the Transitional Article instructs the KI (Information Commission) to be established immediately. Establishment of Provincial Information Commision at least 2 years after the law is enacted. The Government of South Kalimantan Province reflects the order by issuing Local Regulation No. 12 of 2014, regarding the Transparency of Public Information in the Provincial Government of South Kalimantan Province and issuing SK (Letter of Decision) of establishment of Information Commision. The main tasks of Information Commision include: deciding the dispute of public information. In completing the tasks some of the urgent problems examined include: how the motivation of the community using Information Commision services to dispute resolution, how communication patterns resolve information disputes, and what challenges Information Commision in implementing it's task ?. The purpose of the research is to know: community motivation using Information Commision service, communication pattern built by Information Commision, and Information Commision challenge in carrying out the task of resolving information dispute. The results showed: Community motivation using Information Commision services for dispute resolution is quite high, and predicted to increase. 3 (three) communication patterns: written, direct communication and new media built Information Commision quite precisely, effectively, and communicative in resolving information disputes. Not ready and still low awareness of Public Agency on the implementation of Transparency of Public Information Law and the occurrence of differences of perception between the dispute settlement of information that is Information Commision with the Administrative Court of the State Administrative Court (KUN) becomes a major challenge for KI, to encourage Information Commision immediately communicate by sitting one table discussing together the same application of dispute resolution in accordance with the requirements of the Transparency of Public Information Law. Abstrak Undang Undang No 14 Tahun 2008 tentang Keterbukaan Informasi Publik (KIP) pasal Peralihan memerintahkan KI (Komisi Informasi) segera dibentuk. Pemberntu kan KI Provinsi paling lambat 2 tahun sejak peraturan diundangkan. Pemerintah Provinsi Kalimantan Selatan merefleksikan perintah itu dengan mengeluarkan Peraturan Daerah Nomor 12 Tahun 2014, tentang KIP dalam Penyelengaraan Pemerintahan Daerah Provinsi Kalimantan Selatan dan mengeluarkan SK (Surat Keputusan) pembentukan KI. Tugas pokok KI diantaranya : memutuskan sengketa informasi publik. Dalam menyelesaikan tugas tersebut beberapa permasalahan yang urgen diteliti antara lain : bagaimana motivasi masyarakat menggunakan layanan KI terhadap penyelesaian sengketa, bagaimana pola komunikasi menyelesaikan sengketa informasi, dan apa yang menjadi tantangan KI dalam mengimplementasikan tugasnya?. Tujuan penelitian untuk mengetahui : motivasi masyarakat menggunakan layanan KI, pola komunikasi yang dibangun KI, dan tantangan KI dalam melaksanakan tugas menyelesaikan sengketa informasi. Hasil penelitian menunjukkan : Motivasi masyarakat menggunakan layanan KI untuk penyelesaian sengketa cukup tinggi, dan diprediksi terus meningkat. 3 (tiga) pola komunikasi : tertulis, komunikasi langsung dan media baru yang dibangun KI cukup tepat, efektif, dan komunikatif dalam menyelesaikan sengketa informasi. Belum siap dan masih rendahnya kesadaran Badan Publik terhadap pelaksanaan UU KIP dan terjadinya perbedaan persepsi antara lembaga penyelesaian sengketa informasi yakni KI dengan PTUN (Pengadilan Tata Usaha Negara) menjadi tantangan utama bagi KI, hingga mendorong KI segera mengkomunikasikan dengan duduk satu meja membahas secara bersama-sama penerapan penyelesaian sengketa sesuai dengan ketentuan yang dikenhendaki UU KIP.